Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Publisher: Cambridge University Press
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler